Endothelial cell‐specific redox gene modulation inhibits angiogenesis but promotes B16F0 tumor growth in mice. Issue 12 (26th October 2019) - Yura, Yoshimitsu; Chong, Brian S. H.; Johnson, Ryan D.; Watanabe, Yosuke; Tsukahara, Yuko; Ferran, Beatriz; Murdoch, Colin E.; Behring, Jessica B.; McComb, Mark E.; Costello, Catherine E.; Janssen‐Heininger, Yvonne M. W.; Cohen, Richard A.; et al.
Abstract : Glutaredoxin‐1 (Glrx) is a small cytosolic enzyme that removes S ‐glutathionylation, glutathione adducts of protein cysteine residues, thus modulating redox signaling and gene transcription. Although Glrx up‐regulation prevented endothelial cell (EC) migration and global Glrx transgenic mice had impaired ischemic vascularization, the effects of cell‐specific Glrx overexpression remained unknown. Here, we examined the role of EC‐specific Glrx up‐regulation in distinct models of angiogenesis; namely, hind limb ischemia and tumor angiogenesis. EC‐specific Glrx transgenic (EC‐Glrx TG) overexpression in mice significantly impaired EC migration in Matrigel implants and hind limb revascularization after femoral artery ligation. Additionally, ECs migrated less into subcutaneously implanted B16F0 melanoma tumors as assessed by decreased staining of EC markers. Despite reduced angiogenesis, EC‐Glrx TG mice unexpectedly developed larger tumors compared with control mice. EC‐Glrx TG mice showed higher levels of VEGF‐A in the tumors, indicating hypoxia, which may stimulate tumor cells to form vascular channels without EC, referred to as vasculogenic mimicry. These data suggest that impaired ischemic vascularization does not necessarily associate with suppression of tumor growth, and that antiangiogenic therapies may be ineffective for melanoma tumors because of their ability to implement vasculogenic mimicry during hypoxia.—Yura, Y., Chong, B. S. H., Johnson, R. D., Watanabe, Y., Tsukahara, Y., Ferran, B., Murdoch, C. E., Behring, J. B., McComb, M. E., Costello, C. E., Janssen‐Heininger, Y. M. W., Cohen, R. A., Bachschmid, M. M., Matsui, R. Endothelial cell‐specific redox gene modulation inhibits angiogenesis but promotes B16F0 tumor growth in mice. FASEB J. 33, 14147‐14158 (2019). www.fasebj.org